ANALISIS FAKTOR PENYEBAB KECELAKAAN DALAM BIDANG KONSTRUKSI DI PT.X DENGAN MEMPERTIMBANGKAN FAKTOR MANUSIA - Santika Sari; Akhmad Nidhomuz Zaman; Mohammad Rachman Waluyo; Nurfajriah Fajriah (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The Central Statistics Agency states that workers in the construction sector reach 6.9 million or 5.7% of the national workforce. This figure will increase in line with the increasing demand and need for development projects. Thus, the risk of construction accidents is also likely to increase. According to Findley, et al. (2004), the construction industry continues to provide a disproportionate number of fatal and non-fatal work accidents. In ASEAN, Indonesia ranks fifth for the highest construction accidents based on the number of accidents (Endroyo and Tugino, 2007). The high number of work accidents in the construction service industry certainly results in losses of many things. The construction industry in Indonesia should have carried out a more in-depth investigation of the root of the problem so that it can make repairs and the number of accidents decreased. This research will be conducted with the aim of obtaining the causes of accidents in the construction sector using the HFACS method. The factors causing the accident can be input for construction companies. So that later it is hoped that there will be efforts to improve the dominant factors that contribute to accidents. The HFACS model is an accident investigation model based on human error factors. This research is generally divided into 3 stages. The first stage is the preliminary stage, the second stage is the data collection stage which will later be classified into the HFACS taxonomy model, and the third stage is the conclusions and suggestions. The results of this research can provide the dominant causal factors for accidents in each layer. It is hoped that with the results of this research, Indonesian construction companies can make continuous improvement efforts.